Homopolar dihydrogen bonding in ligand stabilized diberyllium hydride complexes, Be2(CH3)2H2L2 (L = H−, CO, N-heterocyclic carbene and CN−). Issue 18 (6th April 2016) - Nijesh, Karikkeeriyil; De, Susmita; Parameswaran, Pattiyil
Abstract : Diberyllium hydride complex – not a diborane analogue: the diberyllium hydrides Be2 (CH3 )2 H2 L2 (L = H −, CO, NHC and CN − ) are isostructural to diborane but differ in the nature of the bonding interaction at the bridging H-atoms. Abstract : The structure and bonding of diberyllium hydride complexes Be2 (CH3 )2 H2 L2, where L = H − (2 ), CO (3 ), NHC (4 ) and CN − (5 ) were studied in detail and compared with isostructural diborane (1 ). The bonding in Be2 (CH3 )2 H2 L2 was analyzed considering the interaction of two Be(CH3 )L fragments with the bridging (μ-H)2 fragment. The geometrical and molecular orbital (MO) analyses indicate that the extent of back donation from Be→L (L = CO, NHC and CN − ) is less in Be2 (CH3 )2 H2 L2 as compared to that in Be(CH3 )L fragments. The NBO, MO and QTAIM analyses indicate a significant charge concentration at the bridging (μ-H)2 in Be2 (CH3 )2 H2 L2, whereas charge depletion is observed at the (μ-H)2 fragment in diborane. The accumulation of electron density at the bridging (μ-H)2 is duly reflected in the detection of a (μ-H)−(μ-H) bond path in Be2 (CH3 )2 H2 L2, in spite of having longer (μ-H)−(μ-H) distances. The interaction between the bridging H-atoms in diberyllium hydride complexes can be considered as homopolar hydride–hydride dihydrogen bonding. The direction of the charge flow is from (μ-H)2 to BH2 in diborane, whereas from Be(CH3 )L to (μ-H)2 in Be2 (CH3 )2 H2 L2 . Hence, the bridging (μ-H)2 fragments in Be2 (CH3 )2 H2 L2 are electron rich as compared to the (μ-H)2 fragment in diborane. The experimental report of the ring opening of the Ar NHC (Ar = 2, 4, 6-trimethylphenyl) ligand through hydride transfer from [Be(CH3 )H( Ar NHC)]2 corroborates well with the presence of electron rich bridging (μ-H)2 in diberyllium hydride complexes.